Evaluation of Summer Season Characteristics and Its Changes in Iraq over the Period (1960-2021) - Al-Jubouri, Hana; Muslih, Khamis (Al-Adab Journal, 2024)
Anthropogenic climate change has essentially affected the characteristics of the thermal seasons, hence the overall ecosystems, and human health. The characteristics of the thermal seasons in Iraq, and how they change are still unclear. This research has been conducted to: (1) evaluate the spatial characteristics of summer season in Iraq over the period (1960-2021). (2) Estimating changes in the length and timing (onset and end) of summer in Iraq using the Mann-Kendall test (MK) and Sen's slope estimator. The findings indicated that there are significant spatial differences in the average length of the summer season in Iraq. The difference reaching more than 30 days between northern and southern Iraq, It is longer in the south. Results of trend analysis showed that summer season length significantly increases by 3.33 and 6.67 days/decade respectively. Our results reveal that, all over Iraq, the onset of thermal summer season occurs earlier by more than 17 days during (1960-2021). The biggest statistically significant changes in summer advancing were observed in northern and western Iraq. However, the results revealed that the only western Iraq has been recorded advancing at the end of the summer, while the end of the summer at all other parts occurred later.